PENGARUH INSTRUMEN MONETER KONVENSIONAL DAN INSTRUMEN MONETER SYARIAH TERHADAP PRODUK DOMESTIK BRUTO PERIODE 2012-2016 - Try Roedyhantoro M; Eko Fajar Cahyono (Universitas Airlangga, 2018)
This study aims to determine that syariah monetary instruments and conventional monetary instruments both have an effect on the Gross Domestic Product in Indonesia. This research uses quantitative approach with Vector Auto Regression (VAR) method. This research be held during January 2012 until December 2016 in Indonesia. There are 5 variables in this research, they are “Sertifikat Bank Indonesia” (SBI) and Reverse Repo “Surat Utang Negara” (SUN) to represent conventional monetary instrument, and the representative of syariah monetary instrument are “Surat Bank Indonesia Syariah” (SBIS) and Reverse Repo “Surat Berharga Syariah Negara” (SBSN) and the last variable is Gross Domestic Product (GDP). The results of this research indicate that only SBI that has a significant positive effect on GDP. While Reverse Repo SUN, SBIS and Reverse Repo SBSN have no significant effect on GDP. REFERENCESBeik, Irfan Syauqi. 2010 ‚Karakter Keuangan Syariah, dalam Tsaqofi Jurnal Iqtishodia. Institut Pertanian Bogor,Bratadharma, A. 2016. Memahami Apa Itu Reverse Repo dan BI Rate, (Online), (http://ekonomi.metrotvnews.com/read/2016/04/15/513924/memahami-apa-itu-reverse-repo-dan-bi-ratehtml, diakses pada tanggal 8 April 2017 pukul 21:44)Chapra, M. Umer. 2000. Sistem Moneter Islam. Gema Insani Press. JakartaChouwdury, Mausudul Alam. 1997. Money in Islam, London: Routledge._________. 2012. Fundamental of Islamic Economics System. Edisi terjemahan oleh Suherman Rosyidi . Penerbit Kencana Prenada Media Group. JakartaDepartemen Agama RI. 2008. Al-Qur’an Terjemahan (Revisi Terbaru) dengan transliterasi Arab-Latin. Semarang CV. As-Syifa’Dernburg, T. 1985. Macroeconomics: Concept, Theoris, and Policies. Edisi ketujuh. McGraw-Hill. New YorkFriedman,M dan Anna Schwartz. 1993. A Monetary History of United States, 1867-1960. Ninth Paperback Printing Edition. Princeton University Press. New JerseyGujarati, D. 2003. Ekonometri Dasar. Terjemahan: Sumarno Zain, Penerbit Erlangga. Jakartahttp://www.bi.go.id/id/moneter/operasi/operasi-pasar-terbuka/Contents/Default.aspx html, diakses pada 13 April 2017http://www.bi.go.id/id/publikasi/perkembangan/Default.aspx html, diakses pada 13 April 2017http://www.bi.go.id/id/statistik/seki/bulanan/Default.aspx html, diakses pada 13 April 2017http://www.bi.go.id/web/id/Moneter/Tujuan+Kebijakan+Moneter/ diakses pada tanggal 7 Maret 2017Karim, Adiwarman A. 2002. Ekonomi Islam Suatu Kajian Ekonomi Makro. Jakarta: The International Institute of Islamic Thought. Indonesia,.Khan, M fahim. 1995. Essay in Islamic Economy. The Islamic Foundation . Islamic Economics Series. LeicesterKostov,P & John Lingard. 2000. Regime-Switching Vector Error Correction Model (VECM). Analysis Of UK Meat.Mankiw,N.G. 2003. Teori Makroekonomi, Terjemahaan. Jakarta: ErlanggaMishkin, F. 1995. The Economics of Money, Banking, and FinancialMarkets. 4th edition, New York: Harper CollinsNanga , M. 2005. Makroekonomi: Teori, Masalah Dan Kebijakan. Penerbit Raja Grafindo Perkasa. JakartaHuda, Nurul dkk. 2008. Ekonomi Makro Islam. Edisi Pertama Penerbit Kencana Prenadamedia Group. JakartaRachman, S. 2017. Pengaruh Instrumen Moneter Ganda Terhadap Jumlah Uang Beredar di Indonesia pada Periode 2009-2016. Skripsi S1 Fakultas Ekonomi dan Bisnis Universitas Airlangga. SurabayaRiadi, M. 2017. Pengertian, Tujuan dan Instrumen Kebijakan Moneter, (Online), (http://www.kajianpustaka.com/2017/01/pengertian-tujuan-dan-instrumen-kebijakan-moneter.html, diakses pada tanggal 2 Mei 2017 pukul 12.21)Samuelson, P and Nordhaus. 2005. Economics. Edisi ke delapan. Penerbit McGraw-Hill International Edition. New YorkSari,E. (2016). Bunga Bank Tak Banyak Turun Meski Mengacu Reverse Repo 7 Hari, (Online), (http://www.cnnindonesia.com/ekonomi/20160802160319-78-148669/bunga-bank-tak-banyak-turun-meski-mengacu-reverse-repo-7-hari/ html, diakses 21 April 2017)Taylor, J.B. 1995. “The Monetary Transmission Mechanism: An Empirical Framework”. Journal of Economic Perspectives, 9Warjiyo, P. 2004. Mekanisme Transmisi Kebijakan Moneter di Indonesia. Seri Kebanksentralan nomor 11. Pusat Pendidikan dan Studi Kebanksentralan (PPSK) Bank Indonesia. Jakarta